Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad. Issue 38 (1st June 2021) - Huber‐Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al.
Abstract: A new base metal iron‐cobalt dyad has been obtained by connection between a heteroleptic tetra‐NHC iron(II) photosensitizer combining a 2, 6‐bis[3‐(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene]pyridine with 2, 6‐bis(3‐methyl‐imidazol‐2‐ylidene)‐4, 4′‐bipyridine ligand, and a cobaloxime catalyst. This novel iron(II)‐cobalt(III) assembly has been extensively characterized by ground‐ and excited‐state methods like X‐ray crystallography, X‐ray absorption spectroscopy, (spectro‐)electrochemistry, and steady‐state and time‐resolved optical absorption spectroscopy, with a particular focus on the stability of the molecular assembly in solution and determination of the excited‐state landscape. NMR and UV/Vis spectroscopy reveal dissociation of the dyad in acetonitrile at concentrations below 1 mM and high photostability. Transient absorption spectroscopy after excitation into the metal‐to‐ligand charge transfer absorption band suggests a relaxation cascade originating from hot singlet and triplet MLCT states, leading to the population of the 3 MLCT state that exhibits the longest lifetime. Finally, decay into the ground state involves a 3 MC state. Attachment of cobaloxime to the iron photosensitizer increases the 3 MLCT lifetime at the iron centre. Together with the directing effect of the linker, this potentially makes the dyad more active in photocatalytic proton reduction experiments than the analogous two‐component system, consisting of the iron photosensitizer and Co(dmgH)2 (py)Cl. This work thus sheds new light on the functionality of base metal dyads, which are important for more efficient and sustainable future proton reduction systems. Abstract : Keeping it simple : A new dyad that is active in photocatalytic proton reduction employing only base metals has been achieved. It connects a tetra‐NHC‐Fe II photosensitizer with a Co III cobaloxime catalyst. The photocatalytic activity is explained by comparison to the equivalent two‐component system and thorough ground‐ and excited‐state characterization.